Searching for a Space for Conversation: A study on how environment affects the articulation of the art experience among opera audiences at The Royal Danish Theatre - Lawaetz, Anna; Gram, Nina; Østerby, Christina (Nordic Theatre Studies, 2017)
“Tell me about your experience in the theatre today”. Even though theatres (with this question) may seek honest, personal, and in depth answers from the audience, this question often results in superficial responds focused on what the audience suspect the theatre wants to hear. It can thus be difficult to get personal and detailed knowledge about the audiences’ experience. In a time, where theatres with different means (co-creation, participation etc.) try to keep audience loyal and engaged, this knowledge is important. In our project, we explore how different situations, locations, questions etc. affect conversations about art experiences and in this article we describe our “search for a space for conversation”. We explore how the space affects the conversation, and how the setting can emphasize certain elements. What happens to the conversation if we sit around an ordinary meeting table, if we walk and talk outside the art institution or if we talk inside the auditorium, where we had the original art experience? This explorative study is part of the project “A Suitcase of Methods”, which is housed by The Royal Danish Theatre and financially supported by The Bikuben Foundation.